FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR - Ayem, Sri; Saefudin, Ahmad (Jurnal Akuntansi, 2023)
This study aims to examine the effect of DER, TATO, company sales growth on financial performance (ROA) in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018-2021. The sample in this study amounted to 73 manufacturing companies listed on the Indonesia Stock Exchange during the 2018-2021 period. This study used purposive sampling technique, which then used the SPSS version 24 application to process data. The result of this research is that DER has a negative effect on the company’s financial performance, TATO has a positive effect on the company’s financial performance, and sales growth has a positive effect on the company’s financial performance.